2017
DOI: 10.5217/ir.2017.15.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide promotes apoptotic cell death and inhibits the migration and invasion of SW620 cells

Abstract: Background/AimsParthenolide (PT), a principle component derived from feverfew (Tanacetum parthenium), is a promising anticancer agent and has been shown to promote apoptotic cell death in various cancer cells. In this study, we focused on its functional role in apoptosis, migration, and invasion of human colorectal cancer (CRC) cells.MethodsSW620 cells were employed as representative human CRC cells. We performed the MTT assay and cell cycle analysis to measure apoptotic cell death. The wound healing, Transwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Consistently, we found that tamoxifen induced migration at low concentrations. PTL was also shown to suppress cell migration and invasion in human cancer cells, and could inhibit focal adhesion kinase‐mediated cell invasion . Similarly, we found that the migration induced by tamoxifen can be inhibited by ACT001.…”
Section: Discussionsupporting
confidence: 64%
“…Consistently, we found that tamoxifen induced migration at low concentrations. PTL was also shown to suppress cell migration and invasion in human cancer cells, and could inhibit focal adhesion kinase‐mediated cell invasion . Similarly, we found that the migration induced by tamoxifen can be inhibited by ACT001.…”
Section: Discussionsupporting
confidence: 64%
“…The cytotoxicity of PT found in our analysis has been confirmed by other investigations. PT caused cells death in SW620 cells by inhibiting migration/invasion proteins such as E-cadherin, β-catenin, vimentin, Snail, cyclooxygenase-2, matrix metalloproteinase-2 (MMP-2), and MMP-9 as well as by activating caspase-3 (Liu et al, 2017). It also showed growth inhibitory effects of human cervical cancer (SiHa), breast cancer (MCF-7) cell lines (Al-Fatlawi et al, 2015), non-small cell lung cancer (GLC-82) (Lin et al, 2017), immortalized keratinocytes HaCaT and melanoma cells A375 (George et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Parthenolide (PN) is a sesquiterpene lactone that is found in flowers and fruits of the traditional herbal medicine fever-few (Tanacetum parthenium). PN acts as a pro-oxidant/ antioxidant that can elicit a protective response in normal cells but adds injury to tumor cells after radiation therapy (197,202,364). For instance, PN induced apoptosis in the AML-French-American-British subtype cancer while sparing normal hematopoietic cells (CD34 + /CD38 -) and progenitor cells (262).…”
Section: Parthenolidementioning
confidence: 99%